“Three Steps Above Heaven? Really? That’s All Tactic!” New Alternative Masculinities Dismantling Dominant Traditional Masculinity’s Strategies - Rodrigues-Mello, Roseli; Bonell-García, Lars; Castro-Sandúa, Marcos; Oliver-Pérez, Esther (Frontiers in Psychology, 2021)
Research on preventive socialization of gender violence has contributed abundant empirical evidence that attraction to violence is common among adolescents. This has meant that “bad guys”, or those who reflect the Dominant Traditional Masculinity model, are chiefly perceived as appealing, while “good guys” are perceived as good friends but not desirable. The mainstream media tends to reproduce this traditional model of affective-sexual relationships, which has harmful effects on young girls concerning gender and sexuality. However, New Alternative Masculinity men are challenging this traditional and unsatisfactory model of affective-sexual relationships. The 2010 Spanish version of the movie Three Steps above Heaven, a good example of this kind of media product, has proven to greatly impact communicative acts among adolescents. This article explores how this influence on adolescents is because the communicative acts about Hache –the main character in the movie– are full of the language of desire, and his own communicative acts are full of violence. On the one hand, we analyze how Three Steps above Heaven employs communicative acts to enhance the attractiveness of Dominant Traditional Masculinity. On the other hand, based on the evidence gathered in a communicative focus group addressed to 15- and 16-year-old female adolescents, we analyze how New Alternative Masculinity men are demystifying Hache and the idea of having a ‘Three Steps Above Heaven’ by demonstrating with the powerful language of desire that men like him employ farce strategies. The article includes evidence from interventions with adolescents where discussion of movies like this, with the involvement of New Alternative Masculinity men and grounded in the language of desire, can transform the perception about the sexual-affective relationship in the movie, thus counteracting their negative influence in terms of attraction to violence.